Chromosomal Aberration Of Workers Occupationally Exposed To Photocopying Machines In Sulur, South India - MYTHILI BALAKRISHNAN,; AYYAPPA DAS, (International Journal of Pharma and Bio Sciences, 2010)
The frequency of chromosomal aberrations (CA) in peripheral blood lymphocytes was performed in a group of workers occupationally exposed to photocopying machines. Samples of peripheral blood were collected from 66 workers out of which 34 were smokers and 32 were nonsmokers and 40 controls. Toxic components of the photocopiers are from their emissions, toners and extremely low frequency electromagnetic fields that cause DNA damage. Our results suggest that there was a significant increase in the chromosomal aberrations in the workers when compared to the controls. DNA frequency of the workers increased with length of the chemical exposure period. The results allowed us to conclude that the individuals studied belong to a risk group and should periodically undergo biological monitoring and appropriate care.